Meningkatkan Literasi Keuangan dan Digital Melalui Komunitas Diaspora Indonesia di Jepang - Dedi Hariyanto; Darusman Darusman; Ferdy Firmansyah (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
This community service program aims to optimize the self-capacity of the Indonesian diaspora in Tsukuba, Japan, by strengthening digital and financial literacy. The program was conducted through educational sessions, practical workshops, mentoring activities, and evaluation using pre-test and post-test methods involving 15 members of PPI Ibaraki. The digital literacy materials focused on social media utilization, personal branding, and digital content creation, while financial literacy materials emphasized personal financial management, budgeting strategies, and safe digital investment practices. Evaluation results demonstrated a significant increase in participant understanding, with average scores improving from 55% to 90%, indicating a 35% increase in knowledge and practical skills. Participants also showed improved abilities in creating productive digital content and managing personal finances more responsibly while living in Japan. The findings indicate that integrated digital and financial literacy training can effectively strengthen the independence and adaptive capacity of Indonesian diaspora communities abroad.